2018
DOI: 10.7326/m18-0400
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians' Perspectives on Providing Emergency-Only Hemodialysis to Undocumented Immigrants

Abstract: Robert Wood Johnson Foundation and Doris Duke Charitable Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 24 publications
1
57
0
1
Order By: Relevance
“…Because of inconsistent, inadequate dialysis, they have endured impaired quality of life, frequent hospitalizations, high rates of access related complications, and increased mortality compared to patients on scheduled dialysis 1-3 . Similar experiences have been reported elsewhere [4][5][6][7][8][9][10] .…”
Section: Local Experience In a Safety-net Hospitalsupporting
confidence: 89%
“…Because of inconsistent, inadequate dialysis, they have endured impaired quality of life, frequent hospitalizations, high rates of access related complications, and increased mortality compared to patients on scheduled dialysis 1-3 . Similar experiences have been reported elsewhere [4][5][6][7][8][9][10] .…”
Section: Local Experience In a Safety-net Hospitalsupporting
confidence: 89%
“…Furthermore, in a qualitative study, physicians who worked in safety-net health care systems where undocumented persons receive emergency dialysis reported that determining when to provide emergency dialysis can cause moral distress. 36 Physicians felt that when required to make decisions about who was to receive emergence dialysis, they were forced to weigh social factors, sacrifice quality of care, and even inappropriately report medical status in order for the patient to qualify for emergency dialysis. 36 Thus, in addition to the moral distress caused by the unavailability of organ retransplantation for patients with undocumented status, physicians face additional stress in providing a suitable medical alternative.…”
Section: Physicians' Responsibilitiesmentioning
confidence: 99%
“…36 Physicians felt that when required to make decisions about who was to receive emergence dialysis, they were forced to weigh social factors, sacrifice quality of care, and even inappropriately report medical status in order for the patient to qualify for emergency dialysis. 36 Thus, in addition to the moral distress caused by the unavailability of organ retransplantation for patients with undocumented status, physicians face additional stress in providing a suitable medical alternative. Moreover, retransplantation is associated with a 50% reduction in mortality relative to remaining on dialysis if the patient survives beyond the 1-year postretransplant period.…”
Section: Physicians' Responsibilitiesmentioning
confidence: 99%
“…Less important, but still relevant, is the effect on providers who deliver care to these patients. Cervantes et al 24 recently outlined some of the experiences of these providers and the moral distress they incur as part of this substandard care, and the contribution to physician burnout from their frustration with the system.…”
Section: Q6b What Logistic Burden Do the Systems Of Emergency Dialysmentioning
confidence: 99%